PATENT "PARASITES" OF DEVELOPMENT INNOVATION - A. Vikulova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This paper examines the activities of patent trolls in the transition to a postindustrial society. The paper determined the impact of patent trolling for development innovative. The study analyzes dynamics of patent lawsuits in the largest high-tech companies in the world over the past five years. Considerable attention is paid to the peculiarities of patent trolling in Ukraine. The paper defines the role of patent trolls in the structure of financing innovation and analyses global instruments to combat patent trolling.